2023
DOI: 10.1097/hc9.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan in liver fibrosis: basic mechanisms, clinical implications, and therapeutic targets

Abstract: Hyaluronan (HA), also known as hyaluronic acid, is a glycosaminoglycan that is a critical component of the extracellular matrix (ECM). Production and deposition of ECM is a wound-healing response that occurs during chronic liver disease, such as cirrhosis. ECM production is a sign of the disease progression of fibrosis. Indeed, the accumulation of HA in the liver and elevated serum HA levels are used as biomarkers of cirrhosis. However, recent studies also suggest that the ECM, and HA in particular, as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…We previously showed that proglumide decreases NASH steatosis by interacting as a partial agonist at FXR ( 39 ). Many of the genes that were significantly downregulated in the livers of DDC-fed mice treated with proglumide were responsible for fibrosis ( Upk3b and HAPLN1 ) ( 40 , 41 ) or inflammation ( Il1f9 ) ( 42 ). Other significantly downregulated genes by proglumide have been implicated as biomarkers in the progression to cirrhosis, such as A1BG (that codes for Alpha-1-B Glycoprotein; 43 ), Ppbp (that codes for proplatelet basic protein; 44 ), and CDC6 (Cell Division Cycle 6; 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that proglumide decreases NASH steatosis by interacting as a partial agonist at FXR ( 39 ). Many of the genes that were significantly downregulated in the livers of DDC-fed mice treated with proglumide were responsible for fibrosis ( Upk3b and HAPLN1 ) ( 40 , 41 ) or inflammation ( Il1f9 ) ( 42 ). Other significantly downregulated genes by proglumide have been implicated as biomarkers in the progression to cirrhosis, such as A1BG (that codes for Alpha-1-B Glycoprotein; 43 ), Ppbp (that codes for proplatelet basic protein; 44 ), and CDC6 (Cell Division Cycle 6; 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some COVID-19 patients were combined with bacterial pneumonia, the slower decline in HA levels may be due to a continued inflammatory process under the double whammy of virus and bacteria ( Misra et al., 2015 ). Since HA has been used as an important diagnostic index to evaluate the degree of hepatic fibrosis, we speculate that persistently high HA levels may be associated with pulmonary consequences, such as lung consolidation and fibrosis ( Bazdyrev et al., 2021 ; Kim and Seki, 2023 ). This evidence highlights the need to reassess HA levels within 3 to 6 months of infection, especially in patients with long COVID.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding to CD44 also promotes fibrogenic, proliferative, and invasive phenotypes of HSCs. In HSCs, the interaction of low-MW HA with CD44 promotes HSC activation by upregulating profibrotic genes, metallopeptidase inhibitor 1, and pro-inflammatory genes such as Mcp-1 and C-X-C motif chemokine ligand 1 [87]. In addition, proteolytic cleavage of CD44 has been reported to occur during HSC activation [23,88].…”
Section: Cd44 Promotes Liver Fibrosismentioning
confidence: 99%